Focal nodular hyperplasia of the liver in men: is presentation the same in men and women?. Issue 6 (1st June 2002) - Luciani, A; Kobeiter, H; Maison, P; Cherqui, D; Zafrani, E-S; Dhumeaux, D; Mathieu, D
Abstract : Background: Focal nodular hyperplasia (FNH) of the liver is a benign hepatic lesion relatively common in women. No studies specifically designed to describe the presentation and imaging findings in males have been published. Aims: The aims of this study were: (a) to describe the clinical and imaging findings in 18 men with FNH, and (b) to compare these data with those observed in 216 women with FNH observed during the same nine year period. Patients and methods: According to a final diagnosis of FNH assessed either by pathological examination or by magnetic resonance (MR), the medical charts of 18 men with FNH observed at our institution were reviewed. In order to compare clinical and MR presentations, the files of 216 women with a total of 291 FNH lesions, investigated during the same nine year period, were reviewed. Results: Eighteen FNH lesions, with a mean diameter of 37.5 mm, were demonstrated in the 18 male patients. A total of 291 lesions with a mean diameter of 63.4 mm were comparatively demonstrated in 216 female patients. Mean age at diagnosis was significantly higher in men (p<0.01) and mean FNH size was significantly smaller in men (p<0.001). Surgery was more frequently performed in men (72.2%) than in women (16.7%) (p<0.001). Conclusions: Our data indicate that FNH is rare in men and that the lesions are smaller and more often atypical than those in women.